Oxytocin Protects Against Isoproterenol-Induced Cardiac Hypertrophy by Inhibiting PI3K/AKT Pathway via a lncRNA GAS5/miR-375-3p/KLF4-Dependent Mechanism - Yang, Yuqiao; Wang, Zhuoran; Yao, Mengran; Xiong, Wei; Wang, Jun; Fang, Yu; Yang, Wei; Jiang, Haixia; Song, Ning; Liu, Lan; Qian, Jinqiao (Frontiers in Pharmacology, 2021)
Cardiac hypertrophy is an ominous escalation of cardiac volume or pressure overload conditions, which can ultimately lead to contractile dysfunction and heart failure. Oxytocin (OT), an endocrine nonapeptide, has been identified as a cardiovascular homeostatic hormone with anti-hypertrophic effects. However, the underlying mechanism remains elusive. In this study, we aimed to investigate the role and mechanism of OT in cardiac hypertrophy. Cardiac hypertrophy model induced by isoproterenol (ISO) were treated with or without oxytocin. Cardiac functional parameters were analyzed by echocardiography. The changes of cell surface area were observed using HE or immunofluorescence staining. The expressions of cardiac hypertrophy markers (BNP, B-Natriuretic Peptide and β-MHC,β-myosin heavy chain), lncRNA GAS5, miR-375-3p, Klf4 were detected by qRT-PCR. KLF4 protein and PI3K/AKT pathway related proteins were detected by Western blotting. The interactions between miR-375-3p with lncRNA GAS5 and Klf4 were verified by dual-luciferase reporter assays. We showed that OT significantly attenuated cardiac hypertrophy, increased expressions of lncRNA GAS5 and KLF4, and decreased miR-375-3p expression. In vitro studies confirmed that either knock-down of lncRNA GAS5 or Klf4，or over-expression of miR-375-3p blunted the anti-hypertrophic effects of OT. Moreover, down-regulation of lncRNA GAS5 promoted the expression of miR-375-3p and inhibited KLF4 expression. Dual-luciferase reporter assays verified the interactions between miR-375-3p with lncRNA GAS5, and Klf4. In addition, OT could inactivate PI3K/AKT pathway. The functional rescue experiments further identified OT regulated PI3K/AKT pathway through miR-375-3p/KLF4 axis. In summary, our study demonstrates that OT ameliorates cardiac hypertrophy by inhibiting PI3K/AKT pathway via lncRNA GAS5/miR-375-3p/KLF4 axis.